PERSEPSI PETANI TERHADAP KINERJA PENYULUH PERTANIAN LAPANGAN DI DESA TALUMELITO KECAMATAN TELAGA BIRU KABUPATEN GORONTALO - Ali, Harisan; Tolinggi, Wawan; Saleh, Yanti (Universitas Negeri Gorontalo, 2018)
This study aims to analyze the level of farmers perceptions and the level of performance of Agricultural Extension Workers in Talumelito Village, Telaga Biru District, Gorontalo District. The study was conducted in October until November 2017 with a sample of 32 farmers who were members of the farmer group. The research method used is survey method. The data analysis used in that is descriptive analysis with percentage formula and Pearson correlation analysis. The results showed that the perception of farmers based on the aspects of knowledge, attitudes and capabilities to the indicators of agricultural extension workers performance in the category enough with a percentage of 74.7%. While the level of agricultural extension performance seen from the aspect of knowledge, attitude and skill of extension to standard of extension performance indicator based on farmer perception is in very good category with percentage equal to 91%. Furthermore, the results of research on the relationship between farmer perceptions and agricultural extension performance showed a relationship between farmers perceptions (x) with agricultural extension performance (y) with the value of the relationship of 0.509 at the 0.05 error level and included in the category of strong correlation / correlation.